Public food transfers during a pandemic: Insights from Bangladesh - Chowdhury, Shyamal; Bin Khaled, Muhammad Nahian; Raghunathan, Kalyani; Rashid, Shahidur (International Food Policy Research Institute, 2021)
Public food transfer program provide a lifeline for the poor in both high- and low-income countries, and many countries stepped these up in response to COVID-19. But little is known about how effective these programs have been in reaching the poor during the crisis. This brief reviews the findings of an evaluation of Bangladesh’s Food Friendly Program, pointing to the difficulties encountered during the pandemic and lessons to help these program perform better in future crises.